Management of disc displacement with reduction and local myalgia using the wax record technique with aluminum wax on stabilization splints and infrared therapy: A case report - Nabilah Fajri Damanik; Ismet Danial Nasution; Ricca Chairunnisa (Indonesia Prosthodontic Association, 2026)
ABSTRACT Background: Disc Displacement with Reduction (DDWR) is one of the most common temporomandibular disorders (TMD), characterized by anterior displacement of the articular disc during mouth opening, typically accompanied by clicking sounds and masticatory muscle pain. DDWR is frequently associated with local myalgia, often worsened by stress and parafunctional habits. Stabilization splints and infrared therapy have demonstrated effectiveness in reducing symptoms. The use of aluminum wax in bite registration helps achieve a stable centric relation, enhancing splint fabrication accuracy. Objective: This case report aims to describe the management of DDWR with local myalgia and arthralgia through bite registration using aluminum wax to support centric relation during stabilization splint fabrication, complemented by infrared therapy. Case Report: A 40-year-old male reported pain in the left cheek and ear, along with clicking during jaw movement for six months. DC/TMD Axis I assessment confirmed DDWR with local myalgia and arthralgia, Axis II revealed psychological stress. Treatment consisted of behavioral counseling, infrared therapy applied to the left masseter, and splint fabrication with bite registration using aluminum wax. Registration was performed using baseplate wax combined with aluminum wax on the occlusal surface to achieve centric relation during articulator mounting. After two weeks, the patient experienced increased mouth opening from 45 mm to 46 mm, reduced muscle tenderness, and improved muscle relaxation. Conclusion: The combination of behavioral counseling, aluminum wax-assisted bite registration for splint fabrication, and infrared therapy proved effective in reducing symptoms and improving mandibular function in a patient with DDWR and local myalgia. Keyword : Disc displacement with reduction; myalgia; arthralgia; aluminum wax; infra-red therapy